In-situ observation of lateral AlAs oxidation and dislocation formation in VCSELs. (July 2022) - Fabbro, Robert; Coppeta, Raffaele; Pusterhofer, Michael; Fasching, Gernot; Haber, Thomas; Grogger, Werner
Abstract: Understanding how defects are generated and propagate during operation in modern vertical cavity surface emitting lasers (VCSEL) is an important challenge in order to develop the next generation of highly reliable semiconductor lasers. Undesired oxidation processes or performance degrading dislocation networks are typically investigated by conventional failure analysis after damage formation. In this works new approach to VCSEL failure analysis, oxide confined high power VCSELs are investigated in-situ at elevated temperatures in a transmission electron microscope. At high temperatures, lateral oxidation of the current confinement layer as well as formation and propagation of dislocations are observed. The experimental results may deepen the understanding of defect generation in VCSELs during stress tests or standard operating conditions. On the other hand, in-situ TEM proofed to be a promising technique to be utilised in future VCSEL failure analysis, possibly leading to the development of improved defect models and increased VCSEL reliability.